Neuroprotective effects of fermented tea in MPTP-induced Parkinson's disease mouse model via MAPK signaling-mediated regulation of inflammation and antioxidant activity. (February 2023) - Lee, Yu-Rim; Moon, Gyo-Ha; Shim, Doobo; Kim, Jong Cheol; Lee, Kwon-Jai; Chung, Kang-Hyun; An, Jeung Hee
Graphical abstract: Highlights: Semi-fermented tea exerts anti-inflammatory, anti-apoptotic, and anti-oxidant activity. Semi-fermented tea showed the highest the level of theanine and GABA composition. Semi-fermented tea alleviated MPTP-induced behavioral impairment and dopaminergic neuronal damage and reduced α-synuclein levels. Abstract: Parkinson's disease (PD) is a neurodegenerative disorder that is characterized by dopaminergic neuronal damage. In this study, three tea extracts from Hadong, Korea, were evaluated in a 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP)-induced neurotoxicity damage model (C57BL/6 mice) for their therapeutic effects against PD: green tea (GT), semi-fermented tea (SFT), and fermented tea (FT). Theaflavin content in the teas increased but catechin content decreased with the degree of fermentation. In addition, SFT showed the highest theanine and γ-aminobutyric acid contents. SFT at a concentration of 25 μg/mL showed the highest activity in the 2, 2-diphenyl-1-picrylhydrazyl radical scavenging assay among all samples. Furthermore, the 2, 2′-azino-bis 3-ethylbenzothiazoline-6-sulfonic acid radical scavenging activity of 25 μg/mL SFT was higher than that of l -ascorbic acid. Fermented tea suppressed the expression of inflammatory cytokines, such as interleukin-6, tumor necrosis factor-alpha, inducible nitric oxide synthase, cyclooxygenase-2, and macrophage-1, as well as inhibited overexpression of apoptotic signals, including p-53, cleaved caspase-3, and poly (ADP-ribose) polymerase-1. Moreover, GT, SFT, and FT regulated the MPTP-induced oxidative stress-related factors, including superoxide dismutase, glutathione-S-transferase, and nicotinamide adenine dinucleotide phosphate oxidase 4. Fermented tea also alleviated MPTP-induced behavioral impairment and dopaminergic neuronal damage and reduced α-synuclein levels. These results indicate that fermented tea is effective for the treatment of neuro-inflammatory, neuro-apoptotic, and neuro-oxidative disorders.